A Bibliometric Analysis of Organizational Citizenship Behavior (OCB) - Anis Sya'bania; Madziatul Churiyah (Jurnal Syntax Transformation, 2022)
OCB is an important behavior carried out by an employee in the company because OCB can improve employee performance and organizational success. Research using bibliometric analysis to offer a broad overview of the topic of OCB for future experiments is still rare. This literature review study aims to provide a broader study of (OCB) using bibliometric analysis. The articles used in this study were compiled from the Scopus database. There were 53 articles found and analyzed in this study from 2018 to 2021. After managing the database from Scopus, the researchers then carried out classification and visualization using VOSviewer software to analyze co-authorship, co-occurrence, and citations. This literature study as a whole can provide references and an overview of OCB in the right company for future research. The results of research using bibliometric analysis are important for academics, researchers, company organizations, and company owners, especially for employees who do OCB. This has the intention that company leaders can find out things related to OCB so that they can provide support to employees who have done OCB, because with good OCB an employee will have a high level of loyalty, for example, individuals will remain loyal even to their organization even though the organization is experiencing difficult conditions